DAMPAK PROGRAM DANA DESA TERHADAP PENINGKATAN PEMBANGUNAN DAN EKONOMI DI KECAMATAN PINELENG KABUPATEN MINAHAS - Feiby Vencentia Tangkumahat; Vicky V. J. Panelewen; Arie D. P. Mirah (Sam Ratulangi University, 2017)
This study aims to analyze the village fund policy, especially on the implementation process of village funds project from planning, disbursement, utilization to accountability. The research was conducted on seven villages receiving the village fund in Pineleng Sub-district, Minahasa District, North Sulawesi Province. This research was conducted for 3 (three) months from January to March 2017. This research uses primary and secondary data. Primary data comes from observations and interviews. The samples in this study were members of the village community in Pineleng Sub-district of Minahasa District in seven villages namely Sea, Sea One, Warembungan, Pineleng Dua Indah, Kali, Kali Selatan and Winangun Atas. Each village takes 10 (ten) respondents for each village so the total number of community members who become sample is 70 (seventy) respondents. The results show that the village fund program in Pineleng Sub-district is running well, but for the future it is necessary to increase the capacity and skill of the village government apparatus in order to support the implementation of this program to improve the economy and better society welfare.